Research on genodermatoses using novel genome‐editing tools. (16th June 2017) - Lehmann, Janin; Seebode, Christina; Emmert, Steffen
Summary: Genodermatoses comprise a clinically heterogeneous group of mostly devastating disorders affecting the skin. To date, treatment options have in general been limited to symptom relief. However, the recent technical evolution in genome editing has ushered in a new era in the development of causal therapies for rare monogenetic diseases such as genodermatoses. The present review revisits the advantages and drawbacks of engineered nuclease tools currently available: zinc finger nucleases (ZFNs), transcription activator‐like effector nucleases (TALENs), meganucleases, and – the most innovative – clustered regularly interspaced short palindromic repeats (CRISPR)‐associated (Cas) nuclease 9 (CRISPR/Cas9) system. A mechanistic overview of the different modes of action of these programmable nucleases as well as their significance for causal therapy of genodermatoses is presented. Remaining limitations and challenges such as efficient delivery and off‐target activity are critically discussed, highlighting both the past and future of gene therapy in dermatology.